Analysis of the parathyroid function in maintenance hemodialysis patients from Changchun, China. Issue 3 (1st September 2017) - Du, Juan; Wang, Songyan; Yu, Wangbo; Li, Shuang; Xu, Jingbo
Abstract: Objective: To evaluate the parathyroid function in maintenance hemodialysis patients from 4 hemodialysis centers and to analyze the cause of the dysfunction. Methods: This cross‐sectional study included patients with chronic renal disease undergoing maintenance hemodialysis treatment at 4 hemodialysis centers in Changchun, China, between March 2014 and August 2015. A total of 337 patients were asked to complete a questionnaire including their name, gender, age, hemodialysis duration, the use of calcium carbonate and vitamin D3 supplements, health education status, hemofiltration frequency, appetite, and education level. Serum intact parathyroid hormone (iPTH), phosphorus, total calcium, blood urea nitrogen (BUN), and creatinine (Cre) levels were obtained from clinical information. Patients with iPTH data were divided into 2 groups: Normal group: the patients with an iPTH level < 100 pg/ml (28 subjects); Abnormal group: the patients with an iPTH level > 100 pg/ml (136 subjects). Intergroup differences were analyzed using the t ‐test. The enumeration data were analyzed by the χ 2 test. Results: The iPTH levels were not monitored for 173 maintenance hemodialysis patients (51.3%) but for 164 patients (48.7%). Of the 164 patients, 28 (17.1%) had a normal serum iPTH level, while the other 136 (82.9%) had an abnormal iPTH level. The maintenance hemodialysis duration and phosphorus levels in the Abnormal group were higher than those in the Normal group ( P  < 0.05). The appetites of patients in the Abnormal group were better than those of patients in the Normal group ( P  < 0.05). Conclusions: A lower proportion of patients on hemodialysis had a normal iPTH level. The phosphorus levels of patients on hemodialysis should be controlled via dietary interventions.